2016
DOI: 10.1371/journal.pgen.1005893
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Imbalance in Regulation of ANRIL through Chromatin Interaction at 9p21 Endometriosis Risk Locus

Abstract: Genome-wide association studies (GWASs) have discovered numerous single nucleotide polymorphisms (SNPs) associated with human complex disorders. However, functional characterization of the disease-associated SNPs remains a formidable challenge. Here we explored regulatory mechanism of a SNP on chromosome 9p21 associated with endometriosis by leveraging “allele-specific” functional genomic approaches. By re-sequencing 1.29 Mb of 9p21 region and scrutinizing DNase-seq data from the ENCODE project, we prioritized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 69 publications
(81 reference statements)
3
31
0
Order By: Relevance
“…Furthermore, while GWAS causal variants have previously been implicated in specific allele-15! specific long-range chromatin interactions 47,[81][82][83][84] , here we report a variant that may directly 16! affect higher-order chromatin architecture.…”
Section: !mentioning
confidence: 99%
“…Furthermore, while GWAS causal variants have previously been implicated in specific allele-15! specific long-range chromatin interactions 47,[81][82][83][84] , here we report a variant that may directly 16! affect higher-order chromatin architecture.…”
Section: !mentioning
confidence: 99%
“…ANRIL is known to function as a recruiter of PRC complexes to facilitate altering of chromatin structure and set the stage for gene regulation (61). Recent "allele-specific" functional genomic studies showed that preferential binding of p300 led to increased interaction of chromatin with ANRIL promoters, thereby activating transcription of the lncRNA (39). We and others have described the regulatory role of ANRIL on the expression of p300, a well-known regulator of FN in diabetic complications (15,24,53).…”
Section: Introductionmentioning
confidence: 98%
“…Emerging studies have shown that long non‐coding RNAs (lncRNAs) play important roles in the occurrence and progression of endometriosis . LncRNAs are a class of non‐coding RNA molecules longer than 200 nt that lack the ability to code protein .…”
Section: Introductionmentioning
confidence: 99%